Students’ colour perception and preference: an empirical analysis of its relationship - Ab Jalil, Nurlelawati; Mohd. Yunus, Rodzyah; S. Said, Normahdiah (Elsevier, 2013)
In learning environment, colour is believe to be able to cause positive or negative behaviour such as avoidance or withdrawal behaviour; affecting performance and stimulate senses. It is learned that visual stimulation contributes to improvement of attention span, develops cognitive abilities and refresh one’s perception towards his environment but varied due to differences of gender and background. This paper focuses on perception and preferences of colours for hostel room as a learning environment amongst undergraduate students at Universiti Teknologi MARA and Universiti Putra Malaysia. It aims to verify the previous findings concerning preference differences among gender in a population and extends the method using visible colour survey. 798 students who are also the hostel residents aged between 19 to 27 years old took part in this random survey. The survey recorded patterns of students’ colour preferences and recommendation colour for their hostel rooms. The preference survey includes 11 colours (red, blue, green, pink, purple, brown, orange, yellow, white, black and gray) together with colour description in value and saturation level with five point Likert scales. Furthermore, the respondents were asked to indicate 12 emotional responses and nominated their preferred colour directly using visible colour survey method from a three dimensional unit of Munsell Colour Tree. The analysis reveals various patterns of colour preferences when the colour options are visible between genders which significantly influence their preference behaviour. The outcomes become the turning point to investigate the effects of colour on students’ alertness during learning activity based on subjects’ preferences and existing colour theory.